Drug Screening Using a Library of Human Induced Pluripotent Stem Cell–Derived Cardiomyocytes Reveals Disease-Specific Patterns of Cardiotoxicity - Liang, Ping; Lan, Feng; Lee, Andrew S.; Gong, Tingyu; Sanchez-Freire, Veronica; Wang, Yongming; Diecke, Sebastian; Sallam, Karim; Knowles, Joshua W.; Wang, Paul J.; Nguyen, Patricia K.; Bers, Donald M.; et al. (Circulation (New York, N.Y.), 2013)
Cardiotoxicity is a leading cause for drug attrition during pharmaceutical development and has resulted in numerous preventable patient deaths. Incidents of adverse cardiac drug reactions are more common in patients with preexisting heart disease than the general population. Here we generated a library of human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) from patients with various hereditary cardiac disorders to model differences in cardiac drug toxicity susceptibility for patients of different genetic backgrounds. Action potential duration and drug-induced arrhythmia were measured at the single cell level in hiPSC-CMs derived from healthy subjects and patients with hereditary long QT syndrome, familial hypertrophic cardiomyopathy, and familial dilated cardiomyopathy. Disease phenotypes were verified in long QT syndrome, hypertrophic cardiomyopathy, and dilated cardiomyopathy hiPSC-CMs by immunostaining and single cell patch clamp. Human embryonic stem cell-derived cardiomyocytes (hESC-CMs) and the human ether-a-go-go-related gene expressing human embryonic kidney cells were used as controls. Single cell PCR confirmed expression of all cardiac ion channels in patient-specific hiPSC-CMs as well as hESC-CMs, but not in human embryonic kidney cells. Disease-specific hiPSC-CMs demonstrated increased susceptibility to known cardiotoxic drugs as measured by action potential duration and quantification of drug-induced arrhythmias such as early afterdepolarizations and delayed afterdepolarizations. We have recapitulated drug-induced cardiotoxicity profiles for healthy subjects, long QT syndrome, hypertrophic cardiomyopathy, and dilated cardiomyopathy patients at the single cell level for the first time. Our data indicate that healthy and diseased individuals exhibit different susceptibilities to cardiotoxic drugs and that use of disease-specific hiPSC-CMs may predict adverse drug responses more accurately than the standard human ether-a-go-go-related gene test or healthy control hiPSC-CM/hESC-CM screening assays.